A Digital Twin Demonstrator to enable flexible manufacturing with robotics: a process supervision case study. Issue 1 (1st January 2021) - Martinez, Santiago; Mariño, Alexis; Sanchez, Sofia; Montes, Ana María; Triana, Juan Manuel; Barbieri, Giacomo; Abolghasem, Sepideh; Vera, John; Guevara, Marco
ABSTRACT: Manufacturing companies are facing different challenges. On the one hand, production is moving from mass-production to mass-customization and personalization. Reconfigurable-, adaptive- and evolving-factories are necessary to achieve the required flexibility. On the other hand, technology must be integrated with human skills to assist the operators in supervising and maintaining manufacturing plants with growing complexity. In line with the Industry 4.0 paradigm, a Digital Twin Demonstrator is proposed to support the supervision activity of the operator in the context of flexible manufacturing with robotics. The supervision is achieved through a Human-Computer-Machine Interaction (HCMI) enabled with the Digital Twin technology. The suggested demonstrator is implemented and validated using a lab case study where it is demonstrated how the proposed HCMI interaction enables 'close-to-real-time' supervision of the manufacturing system in its self-adaptation to production and environmental changes.